Southeast Asian Students’ Perspective in Science and science education - Othman, Mariam; Cyril, Nelson; Mangao, Dominador Dizon; Thoe, Ng Khar; Sinniah, Deva Nanthini; Rajoo, Murugan (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2022)
The study describes the attitudes and beliefs towards science and science education of Year 9 and 10 Southeast Asian students including gender and year level differences based on the seven categories.  This study involved Year 9 and 10 students from seven SEAMEO countries. Out of 5,375 samples selected, 2,158 were boys and 3,217 were girls. There were seven categories in the survey instrument that was administered, including students’ perceptions about: (1) science; (2) science outside school; (3) science topics; (4) scientist vocation; (5) self-efficacy in science; (6) teaching and learning science; as well as (7) future participation in science. The analyses showed that generally students had positive attitudes on categories such as: science, science outside school, teaching and learning science, scientist vocation, science topics and future participation in science. However, in general, the students in this region had slightly low self-efficacy in science in which included items such as science as a difficult subject and science classes are boring.  The results also showed that Year 9 and boys acted more positively than Year 10 and girls in the attitudes and beliefs towards science. Further research and recommendations are explored. The findings would be used as a tool to revise the national science curriculum of the participating countries in terms of content standards and inform teachers of how teaching and learning practices can be aligned with students’ attitudes and perceptions to obtain better learning outcomes. The research findings could also be used as a springboard for further research exploring deeper the variables affecting students’ success in science and providing intervention for teachers’ training curriculum and continuing professional development in terms of technological pedagogical content knowledge (TPACK) that would increase the interest of students in learning and exploring science.